1988
DOI: 10.1073/pnas.85.23.8943
|View full text |Cite
|
Sign up to set email alerts
|

A mutant human proinsulin is secreted from islets of Langerhans in increased amounts via an unregulated pathway.

Abstract: A coding mutation in the human insulin gene (His-B10 -* Asp) is associated with familial hyperproinsulinemia. To model this syndrome, we have produced transgenic mice that express high levels of the mutant prohormone in their islets of Langerhans. Strain 24-6 mice, containing about 100 copies of the mutant gene, were normoglycemic but had marked increases of serum human proinsulin immunoreactive components. Biosynthetic studies on isolated islets revealed that =65% of the proinsulin synthesized in these mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 27 publications
4
90
0
Order By: Relevance
“…Wild-type human insulin shows a sorting index of 0.66 (Powell et al, 1988). Thus, the dimeric insulin B10Asp shows a slightly reduced efficiency of sorting, consistent with earlier published results (Carroll et al, 1988;Gross et al, 1989). Monomeric insulin B9Asp shows a sorting index of 0.67 + 0.02 and therefore is sorted as efficiently as wild-type insulin.…”
Section: Table L Comparison Of the Density Of (Pro)insulin Immunolabesupporting
confidence: 80%
See 4 more Smart Citations
“…Wild-type human insulin shows a sorting index of 0.66 (Powell et al, 1988). Thus, the dimeric insulin B10Asp shows a slightly reduced efficiency of sorting, consistent with earlier published results (Carroll et al, 1988;Gross et al, 1989). Monomeric insulin B9Asp shows a sorting index of 0.67 + 0.02 and therefore is sorted as efficiently as wild-type insulin.…”
Section: Table L Comparison Of the Density Of (Pro)insulin Immunolabesupporting
confidence: 80%
“…Taken together, the data showed that both mutated proinsulins entered the regulated secretory pathway where they are proteolytically processed and localized to densecore secretory granules. The B10Asp data are consistent with those of Carroll et al (1988) and Gross et al (1989) who showed that a significant fraction of the B10Asp was processed into mature insulin within the cells, presumably in dense-core secretory granules.…”
Section: Immunolocalization Of the Proinsulin Variantssupporting
confidence: 79%
See 3 more Smart Citations